Regional Clusters are in Strategy of Achievement of Technological Leadership in Russian Economy - N. Voronina, V.; A. Kononov, M.; V. Bashmakov, D. (International Journal of Engineering and Technology, 2018)
Based on the analysis of different conceptual approaches to the study of the problem of the collapse of the Soviet Union, of introducing into the scientific circulation of new sources, identifies the different factors that determined the events of 25 years ago. We conclude that the conditions of the unfolding scientific and technological revolution demanded the integration of science, education and production, overcoming the departmental barriers, creating a full-fledged innovation system on a national scale. The main areas was to be the development of a General strategy of modernization of the country, the production of modern high-quality products, the implementation of technical renovation of production, resource saving.The article is devoted to the development of a strategy for achieving technological leadership of the regional Russian economy. The necessity of implementing cluster management as a combination of sectoral and territorial management is substantiated with the purpose of creating conditions for effective functioning of the region and the national economy as a whole, resolving the contradiction between resources and the needs of the development of society in the context of globalization. Cluster management is considered as a new form in the regional management system, due to the rapid intellectualization of business processes and the â€œknowledgeâ€ factor in modern business caused by this elevation.Â Â